PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER) DAN CURRENT RATIO (CR) TERHADAP AUDIT DELAY - Renaldi Arindi Putra; Bambang Subiyanto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Audit Delay that exceeds the deadline for POJK provisions number : 14/POJK.04/2022 will result in delays in the publication of financial reports. Delays in the publication of financial reports indicate problems in the company's financial statements, so it takes longer time to complete the audit. The purpose of this study is to obtain empirical evidence and analyze the effect of firm size, return on assets, debt to equity ratio, and current ratio on audit delay. variable audit delay measured by a dummy with the criteria of whether the company crossed the reporting limit or did not cross the 2017-2021 Financial Reporting limit. The total population in this study was 142 companies with 35 companies as research samples, finally the overall observation was 175. This study used secondary data obtained from the Indonesian stock exchange and the official website of each company. Collecting data in this study using a purposive sampling technique. The analysis technique used is logistic regression analysis. Data processing uses the SPSS 26 application. The results show that company size and return on assets have a significant negative effect on audit delay, debt to equity ratio and current ratio have a significant positive effect on audit delay.